Phase transition and complex impedance studies of mechano-chemically synthesized AgI-cuI solid solutions - Johan, Mohd Rafie; Tay, See Leng; Hawari, Nor Liza; Suan, Shahadan (Electrochemical Science Group, 2010)
Solid solutions of AgIx-Cu1-xI (0.1 < x < 1.0) were prepared using mechanochemical technique. XRD measurement shows the AgI-CuI phase system at room temperature. DSC traces show that the superionic phase transition temperature increases from 149 degrees C to 376 degrees C upon addition of Cu. The semicircle of impedance spectra is depressed at higher temperature. Arrhenius plots show a sudden jump in the conductivity around the phase transition temperature.